The Formation of Dajare and Its Effects on Speech Partners in Anime Monogatari Series - Elizabeth Ika Hesti Aprilia Nindia Rini; Aldhimas Kurnia Widianto (IZUMI, 2021)
This study aims to describe the formation of dajare and examine the effects of dajare on speech partners. The data in this study were taken from the anime series entitled Monogatari Series. Data from the anime series were collected using the contextual analysis method. The results showed seven dajare formation processes: homophones, mora change, metathesis mora, combining phrases, dividing phrases, mixing foreign languages, and moving commas. It was found that the effect of dajare on speech partners was mainly positive.